Exploration of Ethnomathematics in Traditional Javanese Cakes - Azurah, Mei Tri Yennita; Maysarah , Siti (Unnes Journal of Mathematics Education, 2024)
Mathematical concepts are used to explore the existence of mathematics in Javanese culture, expecially in traditional Javanese food. Given the current research that discusses traditional Javanese food/cakes is very rare and there is still a lack of public knowledge about ethnomathematics. This study aims to explore the concept of geometry contained in traditional Javanese cakes. This study is qualitative research was conducted in Prapat Janji Village, Buntu Pane District. The instruments used are human instruments. Researchers communicate directly with the object of research and actively participate in data collection, both in literature studies, interviews, documentation, surveys, and observations. The results of this study showed that the traditional Javanese cake there is the concept of flat Geometry on Getuk (Rhombus), Wajik (Parallelogram), Serabi (Circle), Lupis (Triangle), Kue Lumpur (Cylinder), Lemper (Cylinder), Kue Jadah (Cube), Klepon (Sphere), Kue Lapis (Cuboid). Ethnomathematics in traditional Javanese cakes can be used as a source of learning mathematics geometry material.